(untitled) (Research, Society and Development, 2022)
Brazilian beef cattle has increased significantly. As a result, questions about the environmental problems caused by the production of beef on pasture have also increased. The emission of gases that contribute to the greenhouse effect is the main problem of beef cattle. The search for technologies that reduce the emission of gases by cattle and improve the sustainability of the system is growing. Among the studies proposed in this regard, pasture management, the use of fertilizers associated with biotechnologies and the integration of systems have been highlighted. The rotational management has enabled better use of the forage mass, allowing it to maintain the soil cover, preventing its degradation. While the use of nitrogen fertilizers associated with biotechnologies such as the use of growth-promoting bacteria has provided an increase in the cycling of nutrients in the soil, improving the quality of forage reflecting in production. Finally, the use of integrated systems has proved to be an alternative that, in addition to promoting production sustainability, promotes a diversified income for the producer. Thus, the work aims to present information about the use of technologies to minimize the effects of beef production on the environment.